Impact of magnetic fields on the structure of convective atmospheres of red giant stars - Klevas, Jonas; Ludwig, Hans-Günter (Contributions of the Astronomical Observatory Skalnate Pleso, 2018)
We use 3D magnetohydrodynamic CO5BOLD model atmospheres to study the interplay between magnetic fields and convection in the atmospheres of red giant stars. We find that vortex-like structures occur prominently in stars with stronger magnetic fields and lead to alterations of their thermal structures.